Geology of the Parliament Buildings 6. Geology of the British Columbia Parliament Buildings, Victoria - Hora, Zdenek; Hancock, Kirk (Geoscience Canada)

(untitled) (The Geological Association of Canada, 2008)
SUMMARY The British Columbia parliament buildings were constructed in two stages: the first building was started in 1893 and officially opened in 1898; the addition was started in 1912 and completed in 1915. The primary external building stone is a fine-grained, light grey, dacitic volcanic rock, commonly called Haddington Island andesite. The foundation and lower courses are mediumgrained, grey, salt-and-pepper granodiorite, called Nelson Island granite. The Haddington Island andesite was also used for exterior architectural ornaments and statues. A variety of marbles from the USA and Italy decorate the interior of the buildings. Several monuments and fountains within the legislature precinct display a variety of both imported and local provenance building stones. This article presents a brief history of the parliament buildings and their construction, a description of the building stones, and an overview of a century-long performance record of the exterior building stones, which have long resisted the effects of British Columbia coastal weather.